Management of Tax Returns and Payment Letters: Case Study of the Use of SSP in Tax Payments in Indonesia - Sherly Margareta Susanto; Nabilla Aulia Wisnu; Ajeng Maulidya Chandra; Nayla Putri Zahrani; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
In general, tax is a mandatory contribution to the state from individuals or entities that is coercive based on applicable law, with no direct collector of compensation, and is used for state needs within the scope of the people's prosperity law. The SPT itself is a letter used by taxpayers as a report on all forms of tax calculations and payments, both with tax and non-tax objects. SPT can be divided into 2 types, namely Annual SPT and Periodic SPT. Meanwhile, a Tax Payment Letter or what can be called an SSP is proof of payment or deposit of tax that has been made using a form or has been made by other means to the state treasury through a payment place appointed by the Minister of Finance.The aim and objective of carrying out research on the topic of Tax SPT and SSP is to be able to understand the application of SPT, understand the types and functions of SPT, as well as settlement procedures for SPT and our aim is also to understand more about the function of SSP and what the SSP deposit limit is.